2023
DOI: 10.3389/fped.2023.1102354
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of pimecrolimus 1% cream for prevention of transcutaneous sensitization in children with atopic dermatitis during their first year of life

Abstract: IntroductionEpidermal barrier dysfunction in children with atopic dermatitis can cause transcutaneous sensitization to allergens and allergic diseases. We evaluated the effectiveness of an early-intervention algorithm for atopic dermatitis treatment, utilizing pimecrolimus for long-term maintenance therapy, in reducing transcutaneous sensitization in infants.MethodThis was a single-center cohort observational study that enrolled children aged 1-4 months with family history of allergic diseases, moderate-to-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another observational study found that infants aged 1-4 months who received active eczema treatment with topical glucocorticoids for 10 days followed first by maintenance therapy with pimecrolimus 1% cream twice daily for 3 months, and continued on pimecrolimus twice daily three times a week until age 1 year had a lower risk of food allergen sensitization compared with infants who received only reactive treatment with topical steroids during eczema flares. 54 A retrospective study by Miyaji at al. 6 also suggested that early enhanced proactive topical steroid therapy on both clinical and subclinical skin lesions of infants with atopic dermatitis might prevent the onset of food allergy.…”
Section: Eczema Treatment For Food Allergy Preventionmentioning
confidence: 99%
“…Another observational study found that infants aged 1-4 months who received active eczema treatment with topical glucocorticoids for 10 days followed first by maintenance therapy with pimecrolimus 1% cream twice daily for 3 months, and continued on pimecrolimus twice daily three times a week until age 1 year had a lower risk of food allergen sensitization compared with infants who received only reactive treatment with topical steroids during eczema flares. 54 A retrospective study by Miyaji at al. 6 also suggested that early enhanced proactive topical steroid therapy on both clinical and subclinical skin lesions of infants with atopic dermatitis might prevent the onset of food allergy.…”
Section: Eczema Treatment For Food Allergy Preventionmentioning
confidence: 99%
“…The proactive group experienced significant reductions in AD severity, quality of life scores, and serum TARC levels compared with the reactive group. Another observational study found that infants aged 1–4 months who received active eczema treatment with topical glucocorticoids for 10 days followed first by maintenance therapy with pimecrolimus 1% cream twice daily for 3 months, and continued on pimecrolimus twice daily three times a week until age 1 year had a lower risk of food allergen sensitization compared with infants who received only reactive treatment with topical steroids during eczema flares 58 . A retrospective study by Miyaji et al 7 .…”
Section: Introductionmentioning
confidence: 99%